2009
DOI: 10.1097/jcp.0b013e3181abdfd7
|View full text |Cite
|
Sign up to set email alerts
|

Mean Platelet Volume in Patients With Major Depression

Abstract: In this study, normalization of platelet activation is associated with escitalopram treatment for patients with depression. This finding may provide evidence for the use of escitalopram in patients with major depression and comorbid ischemic heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 32 publications
2
38
0
Order By: Relevance
“…In our study, we assessed platelet activity by measuring platelet count and MPV. Our findings were similar to previous studies suggesting that antidepressant treatment reduces platelet (hyper)activity (10,24,31,32).…”
Section: Biochemical Measurementssupporting
confidence: 82%
See 1 more Smart Citation
“…In our study, we assessed platelet activity by measuring platelet count and MPV. Our findings were similar to previous studies suggesting that antidepressant treatment reduces platelet (hyper)activity (10,24,31,32).…”
Section: Biochemical Measurementssupporting
confidence: 82%
“…The effects of stress on circulating white blood cells (WBCs) have been experimentally studied in a number of animal species and or general increases in total WBCs, has been occasionally used as a measure of stress (6,7). volume (MPV) are increased in patients with depression (8)(9)(10). ASR is often seen with depression, and stress-related hormones may fulfil an important role in acute arterial thrombosis by increasing platelet aggregation (2,4,11).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, it has been shown that escitalopram effect of inhibiting reuptake of serotonin occurs in neurons as well as platelets, reducing platelet reactivity (Atar et al, 2006). Besides, as mentioned earlier, patients with depression exhibited normalization of platelet activation and significant reduction in MPV levels after escitalopram treatment (Ataoglu & Canan, 2009), indicating that MPV may play a vital role in pathophysiological process of depression. Thus, considering its role in ischemic stroke as well as depression, MPV may participate in the development of PSD.…”
Section: Discussionmentioning
confidence: 55%
“…Likewise, elevated MPV levels were also found in patients with fibromyalgia syndrome as well as bipolar disorder (Vural et al, 2015; Yildirim, Solmaz, Akgol, & Ersoy, 2016). Furthermore, previous studies showed that MPV levels reduced significantly after antidepressant treatment (Ataoglu & Canan, 2009; Demircan et al, 2016). …”
Section: Discussionmentioning
confidence: 91%
“…Quintana study, from 1992, done on 25 untreated depressive patients, compared to 25 healthy volunteers showed that the concentration of thrombocyte serotonin is lower in depressive patients [33]. The study of Maurej-Spurej et al from 2004, carried out on 27 depressive patients, 13 of which had been untreated and 14 had been taking SIPPS, showed a lower concentration of thrombocyte serotonin in the untreated depressive subjects [34]. In the study presented by Ataoglu and Canan in 2009, they had followed 15 patients suffering from the major depressive disorder, compared them to the group of healthy volunteers and found out that MPV was significantly higher in the group of depressive patients, but no significant difference had been found between the patients and the control group considering the number of thrombocytes [35].…”
Section: Development Of Thrombocytes and Thrombocyte Indicesmentioning
confidence: 99%